INTERKONEKSITAS TASAWUF FALSAFI DAN TASAWUF SUNNI - Ahmad Patih (Karimiyah: Journal of Islamic Literature and Muslim Society, 2022)
Efforts to realign the relationship between Sufism and philosophy have been led by several groups. The most concrete example is Suhrawardi al-Maqtul (11541191 AD) who is prominent in Hikmah al-Isyarqi (philosophy of enlightenment). Philosophical Sufism is a Sufism concept that knows about God (makrifat) with a proportional approach (philosophy) at a higher level, not only knowing God (makrifatullah) but also higher than that, namely ittihad, hullul and wahdatul form (united in form). . Sunni Sufism is a form of Sufism in which Sufis base their Sufism on the Qur'an and As-Sunnah, and link spiritual states (ahwaal) and levels (maqomaah) with these two sources. These two orientations of Sufism are based on the dispositions of the teachings they developed, namely the tendency of religious or moral behavior and the tendency to think. However, both of them have the same goal, namely getting closer to Allah SWT through worship, and trying to purify themselves to achieve peace, happiness and purity of heart by implementing Islamic morality which has implications for improving the morality of oneself and society in all aspects of life, both esoteric and spiritual dimensions. exoteric dimensions that have an impact on social change imbued with social teachings.